WhatsApp sebagai Media Sosial yang Memperkuat Komunikasi Efektif antara Orang Tua dan Anak dalam Keluarga Siagian di Jati Melati, Pondok Melati, Bekasi, Jawa Barat - Siagian, Hasiholan (PROPAGANDA, 2025)
The recent increase in social media usage has led to changes that can lead to effective communication processes, especially in family communication patterns between parents and children. This study explores the role of WhatsApp social media in improving effective communication between parents and children in the Siagian family in Jati Melati, Pondok Gede, Bekasi, West Java. The communication patterns carried out by parents and children utilize WhatsApp social media as a strategic means and communication tool of choice for the family. The use of WhatsApp social media by the Siagian family from Batak Sumatra is felt to be an intensive and easy bridge between parents and children. As a research method used is a case study with a qualitative approach and through in-depth interviews with participants who still live in the same house in the Siagian family in Jati Melati, Pondok Gede, Bekasi. This qualitative study found that WhatsApp facilitates intensive interactions, strengthens relationships, and supports family coordination. The Batak cultural factor that is full of family in the Siagian family has influenced communication relationships and family dynamics in communication patterns that have been felt through the communication process. The results show that WhatsApp can be a catalyst for effective communication with the right usage strategy.